Microfluidic-directed self-assembly of liposomes : role of interdigitation - Lim, Shaun W. Z. (2021)
Microfluidics has been used to process self-assembling liposomal systems that are commonly considered for drug delivery applications. However, it has been found that the parameters of the process are not universally suited for all lipid types. We hypothesize here that size aggregation and instability of microfluidic liposomes are a direct consequence of the presence of interdigitation in these liposomes. Interdigitation refers to the phenomenon where two opposing leaflets of a bilayer interpenetrate into one another and form a single layer. When this happens, aggregation results as the single layer is not thermodynamically stable. Such interdigitation can be induced by pressure, chemicals or by the type of lipid structure. In this study, we systematically investigate the role of lipid composition on membrane interdigitation in order to understand the dependency of lipid interdigitation on liposome formation by microfluidics. By doing so, we use nano DSC and SAXS to probe the extent of lipid interdigitation by measuring the changes in thermodynamics and membrane thickness of the lipid bilayers. Our results show that microfluidic-fabricated liposomes undergo chemical interdigitation in the presence of ethanol, in particular saturated 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC). Strategies to prevent interdigitation is to either remove ethanol above the lipid's main transition temperature (Tm), preventing the formation of interdigitated structures and subsequent aggregated states or by the incorporation of the inhibiting additives, such as cholesterol.